Transcranial Direct Current Stimulation in the Treatment of Subacute Post-Stroke Thalamic Aphasia - Campanella, William (Eur J Case Rep Intern Med, 2020)
BACKGROUND: Although many studies have demonstrated the effectiveness of transcranial direct current stimulation (tDCS) in improving speech recovery in post-stroke aphasia, as far as we know patients affected by thalamic aphasia have never been investigated. PATIENT AND METHOD: A 65-year-old man with severe non-fluent aphasia due to a left thalamic haemorrhagic stroke underwent intensive daily speech therapy combined with tDCS. RESULTS: The patient showed progressive improvement with almost complete recovery of his speech disorder, behavioural disinhibition and apathy. CONCLUSIONS: Our findings suggest that tDCS with concurrent speech therapy can be useful in patients with subcortical stroke lesions. LEARNING POINTS: The thalamus has a central role in the development of the higher functions, such as memory, regulation of behaviour and emotions, and language elaboration. Transcranial direct current stimulation (tDCS) applied to the cerebral cortex is a promising tool for improving language recovery in patients with post-stroke aphasia. Combined treatment with tDCS and speech and language therapy (SLT) was effective in a patient with subacute thalamic aphasia, who showed improvement in all aspects of linguistic and behavioural communication.